Cyber victimization and psychological adjustment difficulties among adolescents: The role of technology mediation and social support from school resource officers. Issue 3 (15th August 2016) - Wright, Michelle F.
Abstract : Purpose: The purpose of this paper is to investigate the buffering effect of the mediation of technology use and social support from school resource officers on the associations between cyber victimization and psychosocial adjustment difficulties (i.e. depression, anxiety, loneliness) over three years (wave-one=sixth grade; wave-two=seventh grade; wave-three=eighth grade). Design/methodology/approach: Participants were 867 eighth graders from the Midwestern USA (ages range from 13 to 15 years old; 51 percent female). Findings: The findings revealed that high levels of wave-two perceived social support from school resource officers and the mediation of technology use made the relationship between wave-one cyber victimization and wave-three depression more negative, while lower levels of this support and less mediation of technology use made the association more positive. These patterns were not found for anxiety and loneliness. Originality/value: Implications for prevention and intervention programs and the role of school resource officers in such programs are also discussed.